Radiation induced damage of the rat heart : biochemistry, function and ultrastructure - Cilliers, George Deiderich (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph.D.(Med.Sc.)) -- University of Stellenbosch, 1990.